Teamwork Approach in Management of Zygomaticomaxillary Complex (ZMC) Fracture with Globe Rupture: A Case Report - Ratna Martina, Nungki; Manalu, Ester P Andyni; Ramadhania, Adilla; Simbolon, Bony P (Lingkar Studi Bedah Plastik Foundation, 2022)
Introduction : Zygomaticomaxillary complex (ZMC) fractures are one of the most common fractures of the facial skeleton. Zygomatic fractures can cause ocular and mandibular functional impairment, along with cosmetic defects. The characteristic clinical signs of zygomatic bone fracture include diplopia, infraorbital nerve paraesthesia, flattening of the cheek, and trismus, whereas maxillary fracture may typically cause flattening of the midface and malocclusion. Therefore, surgical reconstruction is required to restore the function and appearance.Case Report : A 31-year-old man with ZMC fracture and globe rupture underwent open reduction and internal fixation using plate and orbital mesh. We collaborated with an ophthalmologist who performed enucleation and tarsorrhaphy.Discussion : The reconstruction improved functional and physical aspects and therefore psychological wellbeing. The main goal of the ZMC fracture treatment is to reconstruct the face in terms of functions and aesthetic. Furthermore, reconstruction of the left orbit (orbital rims and walls) as a secondary objective despite the blind eye, improved his appearance enabling formation of a pocket into which an eye implant was inserted. Satisfying functional and aesthetic outcome was achieved in this patient.Conclusion: A teamwork approach in surgical reconstruction for this case with ZMC fracture which always has an orbital component, was recommended to obtain an effective and optimal result. Both plastic surgeon and ophthalmologist can elaborate patient needs for facial reconstruction especially orbital region with good result.